APLIKASI ALGORITMA BACKTRACKING UNTUK MENENTUKAN RUTE OPTIMAL DISTRIBUSI AIR ISI ULANG GONZALO DI KOTA AMBON - Jemsry E. Lakotany; Elvinus R. Persulessy; Yopi Andry Lesnussa (Barekeng)
Distribution is a delivery of goods from an original area to the destination area, wherein the distribution, the problem of travel routes is very important because it can affect the time and cost of doing the distribution. The optimal route itself is a route that minimizes the distance and travel time. This research using the Backtracking Algorithm as part of the Traveling salesman problem method in finding the shortest route or minimum distance. In this research, the Backtracking algorithm is applied to search the minimum route for Gonzalo refill water distribution. The results obtained are the path with the shortest route in Ambon City, such as: Gonzalo - Jln. Karang Panjang - Jln. Pitu ina - Jln. Dr. Kayadoe - Terminal mardika - Jln. Wr. Supratman - Jln. A.Y. Patty - Jln. Said Commands - Jln. Pattimura - Jln A. Yani - Gonzalo, with a long of travel route is 15,301 Km.